Investigation of magnetic anisotropy in Co nanoparticles using ferromagnetic resonance technique - Sendilkumar, A.; Kasture, Manasi; Patel, Pitamber; Ramana, Chepuri V.; Bhagavatula L. V. Prasad; Srinath, S. (Journal of Physics: Conference Series, 2010)
Using ferromagnetic resonance (FMR) technique, we have investigated the temperature dependence and angular dependence of line width and resonance magnetic field of Co nanoparticles capped with novel alkane carboxylic acids of varying chain lengths. The magnetic properties such as blocking temperature and anisotropy sensitively depend on the chain length as evidenced by the temperature dependence of line width. These results indicate that the magnetic properties of these samples are critically governed by the interparticle interactions which are decided by the chain length. The presence of anisotropy even up to very high temperature above the blocking temperature observed in these studies confirms the presence of inter-particle magnetic interactions as well as intra-particle exchange interaction between the core and shell regions as evidenced by our earlier ac susceptibility and transverse susceptibility measurements on similar system.